Design of A Cooked Rice Dispenser Device for A Small Food Business - COSLEYCAN, OLIVIA CHEMMA; AZLAN, ENCIK MOHD AZWIR (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Rice is a starchy cereal that is edible and also the main staple for most of the countries all around the world. Many food businesses still serve rice and make it as the main dish in their restaurants but still use the traditional method (manual) to scoop the rice and this causes the price inconsistency, inefficient and low production during peak hour. Manual method also less in aspect of hygiene. The research aims to design a cooked rice dispenser that is able to dispense various amounts of rice faster based on the setting provided and meet the characteristic food hygienic equipment design that can be use in any small food business. By referring design process by George E. Dieter, there is three main part that had been generated in order to complete this project, which is conceptual design, embodiment design and detail design. Other than that, engineering calculation and SolidWorks software are needed in this project for develop the analysis and simulation for the component. The purpose of engineering analysis and simulation is to evaluate the product specification whether it fulfil the requirements or vice versa. The final design of cooked rice dispenser device is expected to dispense cooked rice less than seven seconds. The overall dimension for the device will be 380mm (L)×550mm(W)×606mm(H) with total weight of 23.26 kg. This design is expected to be more efficient when compared to the traditional methods in scooping the cooked rice.